'Something is said ...': A conversation with Maria Chevska. (1st April 2017) - Taylor, Brandon
In this conversation, the painter Maria Chevska and the author discuss the notion of commitment in painting as presented in Sartre's writings of the 1940s, in Chevska's current practice and in her exhibition at the Vane Gallery, Newcastle, England, in 2014, and in the wider world of contemporary painting today. They range over questions of attitude, manner, materials, source material and a recent article by David Joselit on 'transitivity' in painting as a way of achieving contact with the register of contemporary events.